Abacavir, nevirapine, and ritonavir modulate intracellular calcium levels without affecting GHRH-mediated growth hormone secretion in somatotropic cells in vitro. (15th February 2019) - Brigante, Giulia; Riccetti, Laura; Lazzaretti, Clara; Rofrano, Laura; Sperduti, Samantha; Potì, Francesco; Diazzi, Chiara; Prodam, Flavia; Guaraldi, Giovanni; Lania, Andrea G.; Rochira, Vincenzo; Casarini, Livio
Abstract: Growth Hormone (GH) deficiency is frequent in HIV-infected patients treated with antiretroviral therapy. We treated GH3 cells with antiretrovirals (nevirapine, ritonavir or abacavir sulfate; 100 pM-1 mM range), after transfection with human growth hormone releasing hormone (GHRH) receptor cDNA. Cells viability, intracellular cAMP, phosphorylation of CREB and calcium increase, GH production and secretion were evaluated both in basal condition and after GHRH, using MTT, bioluminescence resonance energy transfer, western blotting and ELISA. Antiretroviral treatment did not affect GHRH 50% effective dose (EC50 ) calculated for 30-min intracellular cAMP increase (Mann-Whitney's U test; p ≥ 0.05; n = 4) nor 15-min CREB phosphorylation. The kinetics of GHRH-mediated, rapid intracellular calcium increase was perturbed by pre-incubation with drugs, while GHRH failed to induce the ion increase in ritonavir pre-treated cells (ANOVA; p < 0.05; n = 3). Antiretrovirals did not impact 24-h intracellular and extracellular GH levels (ANOVA; p ≥ 0.05; n = 3). We demonstrated the association between antiretrovirals and intracellular calcium increase, without consequences on somatotrope cells viability and GH synthesis. Overall, these results suggest that antiretrovirals may not directly impact on GH axis in HIV-infected patients. Highlights: Only high doses of antiretrovirals (1 mM) negatively impact on GH3 cells viability. Incubation with antiretrovirals did not affect cAMP levels or CREB phosphorylation. GHRH-mediated intracellular Ca 2+ increase was perturbed by antiretrovirals. Antiretrovirals did not impact intracellular and extracellular GH levels.